Acute onset blindness: a case of optic neuritis and review of childhood optic neuritis. (4th October 2016) - Ramdas, Sithara; Morrison, Danny; Absoud, Michael; Lim, Ming
Abstract : Optic neuritis (ON) is an acquired disorder of the optic nerve due to inflammation, demyelination or degeneration. We report a child who presented with acute onset bilateral visual loss who, following a diagnosis of ON, was treated and had excellent visual recovery. Paediatric ON is considered to be different clinical entity to adult ON. Although in children ON is usually parainfectious or postinfectious, it can be the first presenting feature of multiple sclerosis or neuromyelitis optica spectrum disease. In this paper, we discuss the literature on treatment of ON and prediction of risk of recurrence.